Estudo retrospectivo e in vitro da resposta imune uterina em cadelas com desordens reprodutivas no município de Uberlândia - MG - Costa, Álisson de Souza (2018)
Dogs are currently one of the most important pets in the world, having relevance as pet animals, guard, research and breeding, among others. This increases the demand for new studies on the species, especially regarding uterine diseases, common in animals and important for causing infertility, abortion, preterm labor and clinical disease. The uterine diseases most frequently found in non-pregnant females are pyometra and cystic endometrial hyperplasia, so it was objectified in the first article to determine the casuistry of the reproductive diseases of bitches attended at the Veterinary Hospital of the Federal University of Uberlândia, during six years of evaluation (2012-2017) in order to identify which diseases are most frequent. For this purpose, information on species, age, race and sex of 32.944 animals was consulted. Of these, 16.480 were female canines and 1.185 was diagnosed with alterations in the reproductive system. The animals were divided according to age in four groups (puppies, young adults, adults and elderly); (Group 1 - alterations of the vagina and vulva, Group 2 - alterations of estral cycle, ovary and uterus, Group 3 - alterations of the gestational period and childbirth). The rate of reproductive alterations in the study population was 7.2%, where the mean ages that presented the highest occurrence of diagnoses were in young adult bitches (1 to 5 years old) with 47%. The most frequent pathologies in canine females were pyometra (48.8%), dystocia (13.6%) and Transmissible Venereal Tumor (TVT) (12.6%). Crossbred animals were the most affected by disturbances of the reproductive system, representing 60% of the total females diagnosed. According to these data, the second article aimed to evaluate the effect of inflammation on the production of interleukins 6 (IL6) and 12 (IL12) in cultures of canine endometrial ex vivo challenged with LPS. For the study, 42 healthy canine females submitted to elective ovariosalpingohisterectomy (OSH) were collected from which explants that were submitted to treatment with control, LPS, dexamethasone, LPS + dexa were collected, and the values of IL- 6 and IL-12 by the ELISA method. Explants were classified histopathologically as to the type of inflammation in, without inflammation, acute inflammation, sub-acute inflammation and chronic inflammation. The results revealed that the challenge with LPS did not trigger significant synthesis of IL12 and mainly IL6 in cultures of inflamed endometrial samples, indicating that bitches with inflammatory infiltrate in the endometrium may present impaired innate immune response.